Histological analysis of the tibial anterior cruciate ligament insertion - Oka, Shinya; Schuhmacher, Peter; Brehmer, Axel; Traut, Ulrike; Kirsch, Joachim; Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2016)
This study was performed to investigate the morphology of the tibial anterior cruciate ligament (ACL) by histological assessment.
Published online 2015
Gesehen am 07.07.2020